Sharp Bounds for Generalized m-Linear n-Dimensional p-Adic Hardy-Littlewood-Pólya Operator - Xiang Li; Xiran Zhang; Qianjun He (Journal of Function Spaces)
In this paper, we study the sharp bounds for the generalized m-linear n-dimensional p-adic Hardy-Littlewood-Pólya operator on central and noncentral p-adic Morrey spaces with power weight. As an application, the sharp bounds for the p-adic Hardy-Littlewood-Pólya operator on corresponding Morrey spaces are obtained. These results generalize substantially some well-known results.